Disability as a Romantic Attraction in Jojo Moyes' Novel Me Before You - Suhermen, Retno; Wahyuni, Delvi (English Language and Literature, 2024)
This study is an analysis of Jojo Moyes’ novel “Me Before You” (2012). The purpose of this study is to examine how disability is depicted as a romantic attraction in the novel. This study uses a descriptive-qualitative approach by utilizing feminist disability theory to analyze the novel, and is supported by feminist theory and patriarchal ideology. The results of the study show that the disability depicted in the novel actually becomes a romantic attraction, because physical limitations create a sense of dependence and strength in the relationship. This novel also illustrates that besides disability, there are other aspects that becomes romantic attractions, such as personality, emotional connections, feeling of being appreciated and needed, and sharing experiences. These findings indicate that disability is not a barrier for someone to feel romantic attraction in a relationship, even disability itself can be a source of attraction.